دور النفقات العمومية في تحقيق الاستقرار الاقتصادي الكلي في الجزائر للفترة 2001-2022 - زينب بدرة (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة إلى تحديد دور النفقات العامة في تحقيق الاستقرار الاقتصادي بالجزائر خلال الفترة 2001 -2022، وذلك من خلال أثر متغير النفقات العامة على مؤشرات الاستقرار الاقتصادي الممثلة بمربع كالدور لأهداف السياسة الاقتصادية الكلية، وكذلك دراسة تطور النفقات العامة ومدى تأثيرها على المؤشرات الاقتصادية الكلية: معدل النمو الاقتصادي؛ معدل التضخم؛ معدل البطالة؛ ووضعية ميزان المدفوعات. وقد انتهت هذه الدراسة إلى خلاصة أساسية مفادها أن السياسة الاقتصادية المطبقة في الجزائر خلال هذه الفترة قد ارتكزت بشكل واضح على دعم الطلب الكلي دون العرض الكلي. " "This study aims to determine the role of public expenditures in achieving economic stability in Algeria during the period 2001-2022, through the effect of the public expenditure variable on stability indicators Economic analysis represented by the Kaldor square of macroeconomic policy objectives, as well as studying the development of public expenditures The extent of its impact on macroeconomic indicators: economic growth rate; inflation rate; Unemployment rate; and the balance of payments position. This study concluded with a basic conclusion that the economic policy applied in Algeria during this period, it was clearly based on supporting aggregate demand without aggregate supply "
Keywords: النفقات العمومية، الاستقرار الاقتصادي ،مؤشرات اقتصادية ، برامج تنموية Public expenses; Economic stability; economic indicators; development programmers.